Kinerja Penyuluh Pertanian Lapangan di Kabupaten Sorong Provinsi Papua Barat Daya - Holle, Yolanda (Jurnal KIRANA, 2024)
The goal of developing a sustainable agricultural system requires quality potential human resources. The creation of potential human resources can be achieved through the availability of reliable, quality extension workers, business managers, business organization managers and entrepreneurial managers in the agricultural sector. Therefore, the demands of professional extension workers in carrying out their main tasks and functions must be carried out properly to achieve maximum performance. The study aims to evaluate the performance of field agricultural extension workers and the factors that influence the performance of field agricultural extension workers in Sorong Regency. The study was conducted using a census technique on 73 field agricultural extension respondents consisting of 56 agricultural extension respondents and 17 livestock extension respondents. Data analysis used descriptive tabulation to answer the first objective, followed by PLS (Partial Least Square) analysis to answer the second objective. The results of the study showed that the overall performance of field agricultural extension workers in Sorong Regency was in the moderate category. Internal factors of age, formal education, and length of service had a positive effect on the performance of extension workers at the preparation, implementation and evaluation/reporting stages. External factors of awards and coaching/supervision had a positive effect on the performance of extension workers at the implementation and evaluation/reporting stages. There is also a positive influence between the performance of extension workers at the implementation stage and the evaluation/reporting stage